Developing nursing and midwifery students' capacity for coping with bullying and aggression in clinical settings: Students' evaluation of a learning resource. (March 2018) - Hogan, Rosemarie; Orr, Fiona; Fox, Deborah; Cummins, Allison; Foureur, Maralyn
Abstract: An innovative blended learning resource for undergraduate nursing and midwifery students was developed in a large urban Australian university, following a number of concerning reports by students on their experiences of bullying and aggression in clinical settings. The blended learning resource included interactive online learning modules, comprising film clips of realistic clinical scenarios, related readings, and reflective questions, followed by in-class role-play practice of effective responses to bullying and aggression. On completion of the blended learning resource 210 participants completed an anonymous survey (65.2% response rate). Qualitative data was collected and a thematic analysis of the participants' responses revealed the following themes: 'Engaging with the blended learning resource'; 'Responding to bullying' and 'Responding to aggression' . We assert that developing nursing and midwifery students' capacity to effectively respond to aggression and bullying, using a self-paced blended learning resource, provides a solution to managing some of the demands of the clinical setting. The blended learning resource, whereby nursing and midwifery students were introduced to realistic portrayals of bullying and aggression in clinical settings, developed their repertoire of effective responding and coping skills for use in their professional practice. Highlights: Students reported difficulties coping with bullying/aggression in clinical settings. A blended learning resource was developed to enhance students' capacity for coping. Nursing and midwifery students ( n = 210 ) evaluated the blended learning resource. Reported an increased understanding of coping strategies. Benefits are students may feel more confident when dealing with bullying/aggression.